Gut microbiota and its influence on the Gut-Brain axis in comparison with chemotherapy patients and cancer-free control data in Breast cancer—A computational perspective - Tamizhini Loganathan; George Priya Doss C (PLoS ONE, 2025)
Breast cancer (BC) continues to be a major cause of cancer-related illness and death among women worldwide. Traditional treatments include surgery, radiation, hormone therapy, and chemotherapy, but these approaches often face challenges due to variability in patient response and adverse effects. This study investigated the relationship between gut microbiome diversity, community composition, and pathway analysis in women undergoing chemotherapy for BC (During Treatment-DT) compared to cancer-free controls (CFC). Using 16S rRNA amplicon sequencing, the study assessed alpha and beta diversity. Results showed differences in microbiome composition between DT and CFC samples, with Firmicutes being highly abundant in both groups. Core microbiome and correlation analysis at the phylum and genus levels identified significant microbiota. Specifically, the abundance of genera such as Pseudomonas and Akkermansia decreased, while Ruminococcus and Allistipes increased, as determined by statistical and machine learning approaches. Disease associations were examined based on KO abundance, identifying links to conditions such as autism spectrum disorder, Clostridium difficile infection, chronic kidney disease, and multiple sclerosis. Key KEGG pathways enriched in DT and CFC groups included the two-component system, tyrosine metabolism, and the pentose phosphate pathway. Conversely, dysbiosis or the presence of pathogenic bacteria (Ruminococcus) associated with the SOX8 gene could lead to chemoresistance, altered metabolic pathways, and increased toxicity. These findings underscore the potential implications for treatment outcomes and personalized medicine.